Identification Of Leading Sectors As The Growth Pole Of Ambon City - Izaac Tony Matitaputty; Dientje Rumerung; Hermi Oppier; Fredy H Louhenapessy (International Journal of Social Service and Research, 2023)
A growth pole is an area experiencing rapid expansion and is seen as a hub for development, with the potential to influence the development of neighboring areas. This research aims to identify key sectors that can serve as the economic driving force in Ambon city. The study utilized historical data, specifically time series data from the gross regional domestic product (GRDP) in 2010 constant prices. The research methodology employed several techniques, including Location Quotient (LQ) analysis, Dynamic Location Quotient (DLQ) analysis, and Klassen Typology analysis, to assess the prominent sectors in Ambon city. Additionally, the Shift-Share Analysis (SSA) approach was used to estimate the impact of these leading sectors on the city's economic growth. The LQ analysis revealed the existence of ten leading sectors in Ambon city. Furthermore, the Klassen Typology analysis categorized these sectors into five developed, five stagnant, five developing, and two underdeveloped sectors. The SSA analysis indicated that four sectors had the highest share value in the province's share component, four sectors showed positive values in the proportional shift component, and eleven sectors exhibited positive values in the differential shift component. The cumulative effect of these three components illustrates the significant impact of these sectors on Ambon city's economic growth.